History and Narrative in Japanese - Kumakura, Chiyuki (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1995)
This essay analyzes what Oe Kenzaburo (1994 Nobel laureate in literature) calls two opposing poles of ambiguity. The modernization of the Japanese language has been oriented toward learning from and imitating Indo-European languages (or Chinese), which permits one to make objective statements. Yet native Japanese (yamato kotoba) is unequivocally oriented by the speaker's standpoint which is naturally subjective, reflecting only his/her perceptions and judgments. To Oe, this ambiguous orientation of the Japanese language has forced its culture into obscurity and isolation. In my analysis, the "interpersonal" nature of Japanese (derived from the speaker orientation) and the interpersonal culture of Japan (derived from the language) have created a culture that appears ambiguous and may often be considered inscrutable from a European perspective. However, interpersonality as a feature of Japanese culture and in Japanese discourse is a new concept that deserves further examination.